2010
DOI: 10.14295/bds.2004.v7i4.213
|View full text |Cite
|
Sign up to set email alerts
|

Microleakage evaluation of composite restorations submitted to load cycling

Abstract: The aim of this research was to evaluate the load cycling influence in resin composite restorations through marginal leakage analysis, in enamel and cementum. Forty bovine incisors were allocated in four groups (n=10): I – Z250 resin composite / Single Bond adhesive system; II – Charisma resin composite / Gluma One Bond adhesive system; III - Z250 resin composite / Single Bond adhesive system submitted to 1,000 cycles (10Kgf); group IV - Charisma resin composite / Gluma One Bond adhesive system submitted to 1,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
0
0
4

Year Published

2016
2016
2019
2019

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 9 publications
1
0
0
4
Order By: Relevance
“…In the present study, after applying mechanical load cycling, the occlusal and gingival microleakage of Z350 increased (not signifycantly). These findings were in agreement with those of previous studies [12,13, 16,2325]; however, a number of studies have reported that microleakage of composite restorations increases under mechanical load cycling [15,16, 26]. These differences in the results of experimental studies could be related to variations in the tested restorative materials, the magnitude of the applied force, method of force application and cavity preparation and evaluation technique.…”
Section: Discussionsupporting
confidence: 91%
“…In the present study, after applying mechanical load cycling, the occlusal and gingival microleakage of Z350 increased (not signifycantly). These findings were in agreement with those of previous studies [12,13, 16,2325]; however, a number of studies have reported that microleakage of composite restorations increases under mechanical load cycling [15,16, 26]. These differences in the results of experimental studies could be related to variations in the tested restorative materials, the magnitude of the applied force, method of force application and cavity preparation and evaluation technique.…”
Section: Discussionsupporting
confidence: 91%
“…A seleção dos sistemas adesivos e dos materiais restauradores se fundamentou no conhecimento de suas propriedades e em sua larga utilização em pesquisas laboratoriais e clínicas (HEYMANN et al, 1991;FRUITS et al, 2002;SCHNEIDER et al, 2004). A escolha do dente se baseou em estudos prévios que mostraram maior prevalência de lesões de abfração em pré-molares (ICHIM et al, 2007;GOEL;KHERA;SINGH, 1990), os quais são geralmente encontrados em grande quantidade em Bancos de Dentes devido à sua indicação para extração por razões ortodônticas.…”
Section: Discussionunclassified
“…Esse achado era esperado porque na região cervical, quando existe esmalte, este tem pouca espessura, mas demonstra alguma estabilidade à interface material/dentina circundando toda a restauração (De MUNCK et al, 2003). Isso pode ser explicado, porque o esmalte apresenta pouco conteúdo orgânico, baixa umidade, homogeneidade e ainda, pelas irregularidades superficiais propícias à permeação do adesivo, quando da técnica de condicionamento ácido, que garante êxito no mecanismo de adesão (SCHNEIDER et al, 2004;VAN MEERBEEK et al, 2003) e redução significante da microinfiltração (HEMBREE, 1980;LEINFELDER, 1994).…”
Section: Discussionunclassified
See 2 more Smart Citations